2004
DOI: 10.1021/ar0300524
|View full text |Cite
|
Sign up to set email alerts
|

Theory of Asymmetric Organocatalysis of Aldol and Related Reactions:  Rationalizations and Predictions

Abstract: Computational studies have led to models to understand some classic and contemporary asymmetric reactions involving organocatalysts. The Hajos-Parrish-Eder-Sauer-Wiechert reaction and intermolecular aldol reactions as well as Mannich reactions and oxyaminations catalyzed by proline and other amino acids, and Diels-Alder reactions catalyzed by MacMillan's chiral amine organocatalysts have been studied with density functional theory. Quantitative predictions for several new catalysts and reactions are provided.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

4
171
1
7

Year Published

2006
2006
2016
2016

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 462 publications
(183 citation statements)
references
References 71 publications
4
171
1
7
Order By: Relevance
“…1, and has inspired the development of many other catalysts for a myriad of selective transformations [2]. Computational studies [3] have suggested a mechanistic analogy to reactions of aldolase enzymes [4]. Our recent work provided the first kinetic support for the enamine mechanism in aldol reactions and clarified the role of water on and off the catalytic cycle [5,6].…”
mentioning
confidence: 96%
“…1, and has inspired the development of many other catalysts for a myriad of selective transformations [2]. Computational studies [3] have suggested a mechanistic analogy to reactions of aldolase enzymes [4]. Our recent work provided the first kinetic support for the enamine mechanism in aldol reactions and clarified the role of water on and off the catalytic cycle [5,6].…”
mentioning
confidence: 96%
“…However, only a few studies [1][2][3][4][5][6][7][8][9][10][11] of synthetic reactions using unprotected (free) amino acids have been reported. Most of the synthetic transformations to natural products, pharmaceuticals, and chiral auxiliaries have been performed [12][13][14][15] with protected amino acids to increase solubility in organic solvents and avoid side reactions.…”
mentioning
confidence: 99%
“…18 Whilst a universally accepted mechanism for the HPESW reaction remains elusive, the most widely cited mechanistic pathway for conversion of 1 into 2 involves the carboxylic acid-facilitated formation of an enamine intermediate, the initial step of which involves the nucleophilic attack of the carbonyl of 1 by the nitrogen lone pair of electrons in proline. 19 In addition, proline possesses both acidic and basic properties and can consequently influence the propensity of dehydration of the ketal into the ketone. Therefore, the precise balance between nucleophilicelectrophilic and acid-base properties of proline are essential in order to control the HPESW reaction, with the conversion of 1 into 2 being determined by nucleophilicity of the nitrogen and 2 into 3 being controlled by the availability of the proton (i.e.…”
Section: Introductionmentioning
confidence: 99%